Red-emitting chimeric firefly luciferase for in vivo imaging in low ATP cellular environments - Branchini, Bruce R. (Anal Biochem, 2017)
Beetle luciferases have been adapted for live cell imaging where bioluminescence is dependent on the cellular availability of ATP, O(2), and added luciferin. Previous Photinus pyralis red-emitting variants with high K(m) values for ATP have performed disappointingly in live cells despite having much higher relative specific activities than enzymes like Click Beetle Red (CBR). We engineered a luciferase variant PLR3 having a K(m) value similar to CBR and ~2.6-fold higher specific activity. The red-emitting PLR3 was ~2.5-fold brighter than CBR in living HEK293T and HeLa cells, an improvement consistent with the importance of the K(m) value in low ATP environments.